2013
DOI: 10.1016/j.ijgo.2013.03.028
|View full text |Cite
|
Sign up to set email alerts
|

Bakri balloon tamponade for the management of postpartum hemorrhage

Abstract: Maternal mortality a -0.46 (0.004) -0.36 (0.063) West: -0.63 (0.008) West: -0.69 (0.013) East: -0.24 (0.478) East: 0.04 (0.919) Central: 0.75 (0.246) Central: 0.99 (0.037) Southern: -0.80 (0.101) Southern: -0.67 (0.327) Neonatal mortality b -0.39 (0.019) -0.30 (0.119) West: -0.55 (0.027) West: -0.53 (0.079) East: -0.04 (0.912) East: -0.24 (0.539) Central: -0.92 (0.080) Central: -0.98 (0.116) Southern: -0.52 (0.369) Southern: -0.23 (0.773) Early neonatal mortality b -0.31 (0.062) -0.22 (0.254) West: -0.47 (0.06… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 5 publications
4
11
0
Order By: Relevance
“…The overall success rate of intrauterine balloon tamponade in our series was consistent with rates in other previous small studies, which have ranged from 60 to 94% (Table ). The hysterectomy rate ( n = 11; 22%) was, however, higher than in other series.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The overall success rate of intrauterine balloon tamponade in our series was consistent with rates in other previous small studies, which have ranged from 60 to 94% (Table ). The hysterectomy rate ( n = 11; 22%) was, however, higher than in other series.…”
Section: Discussionsupporting
confidence: 91%
“…Although balloon tamponade has been used routinely for many years in several countries, little is known about its efficacy or the factors that predict its failure. Because only a few single‐center case series, including limited cohort studies, have been reported in the literature, their generalizability is limited . Moreover, only two studies have assessed results for fertility outcomes for women who have undergone balloon tamponade for severe PPH , so this uterus‐sparing procedure may, by modifying the uterine cavity, have still‐undiscovered long‐term effects.…”
Section: Introductionmentioning
confidence: 99%
“…It is also possible that lower resistance balloon may be safely filled to higher than the recommended volumes without rupturing. Higher than recommended filling volumes have been reported in the literature, 12,[27][28][29][30][36][37][38] and our data demonstrate that of the non-Foley balloons, rupture did not occur until at least 2,850 mL had been instilled.…”
Section: Discussionsupporting
confidence: 59%
“…1). [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Twelve articles were included for analysis. 4,[22][23][24][25][26][27][28][29][30][31][32] Eight of the twelve articles (67%) were retrospective analyses of Bakri balloon placement.…”
Section: Resultsmentioning
confidence: 99%